THE EFFECT OF ELECTRIC WELDING AND ASITYLINE WELDING RESULTS ON STEEL PLATES ON HARDNESS TESTS, MICRO STRUCTURE AND TENSILE TEST: PENGARUH HASIL PENGELASAN LAS LISTRIK DAN ASITILIN PADA PELAT BAJA TERHADAP UJI KEKERASAN, STRUKTUR MIKRO DAN UJI TARIK - Will Fernando Marbun (LPPM UPMI, 2023)
In this research, the test material used was St 37 steel plate with a size of 200 mm × 40 mm × 4 mm with a total of 8 (eight) specimens and a size of 100 mm × 40 mm × 4 mm with a total of 2 (two) specimens. This hardness test aims to determine the hardness of the test object in each area, namely the weld area, HAZ and parent metal. This hardness test was tested using a Rockwell A hardness tester (KT 7001 L50 Tc CH, Universal Testing Machine INC Taiwan), using a 120O diamond cone penetrator, pressing load 60 kg, pressing time 5 seconds. From the test results data on the parent metal, the hardness of the test object before the welding process has a lower hardness value compared to the test object after the welding process. In the weld area using electric welding, the average hardness figure was found to be greater than the HAZ area and base metal, while using acetylene welding it was also greater in the weld area than the HAZ area and parent metal, because the weld area experienced high temperature changes due to heat. which arises from the welding itself and experiences relatively fast cooling, while the HAZ area does not experience high hardness, because this area only experiences heat propagation from the weld area. The parent metal has low hardness because this area experiences slight changes in structure and properties along with relatively reduced heat propagation from the weld area. From the two welding systems, namely using acetylene welding and electric welding, it can be seen that the highest average hardness value is for the acetylene base. Tensile strength is one of the properties of materials that can be used to determine the characteristics of materials when subjected to loading. The strength of a material can be seen from its tensile strength value, the higher the tensile strength, the stronger the material. In electric welding, the hardness in the weld area is 45.3 HRA, the HAZ area is 44.8 HRA and the parent metal area is 42.9 HRA. In electric welding and acetylene welding, the average hardness value in the weld area is greater in acetylene welding, in the HAZ area the average hardness value is almost the same, in the parent metal the average hardness value is greater in electric welding.